Faktor-Faktor Yang Berpengaruh Terhadap Kinerja Aparatur Sipil Negara Pada Sekretariat Daerah Provinsi Sulawesi Selatan - Natsir Muhammad; Nur Alam (Jurnal Mirai Management, 2022)
Abstract Method of data collection in this study is a questionnaire, interviews and documentation. Methods of data analysis using the method of descriptive and quantitative methods with multiple linear regression analysis used to measure the factors that Affect the performance of the Employees At the Bureau of Government Secretariat Area of South Sulawesi province which consists of motivation, commitment and work environment of the organization. Based on a test of the free variable F (motivation, work environment and organizational commitment) together have a positive and significant influence against variables bound (employee's performance). Through testing (R) correlation coefficient obtained that level of correlation or relationship between motivation, work environment and employee Performance Against organizational commitment is a high relationship i.e. were 84.1%. And organizational commitment is the most dominant factor affecting the performance of the Employees At the Bureau of Government Secretariat Area Area of South Sulawesi province. Keywords: motivation, work environment, commitment of the organization and performance.